2012
DOI: 10.1016/j.chembiol.2012.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Codon Randomization for Rapid Exploration of Chemical Space in Thiopeptide Antibiotic Variants

Abstract: SUMMARY Thiopeptide antibiotics exhibit a profound level of chemical diversity that is installed through cascades of posttranslational modifications on ribosomal peptides. Here we present a technique to rapidly explore the chemical space of the thiopeptide GE37468 through codon randomization, yielding insights into thiopeptide maturation as well as structure and activity relationships. In this incarnation of the methodology, we randomized 7 residues of the prepeptide coding region, enabling the generation of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 51 publications
(84 reference statements)
2
94
0
5
Order By: Relevance
“…(1417) Biosynthetic engineering of thiopeptides has rapidly emerged as an effective strategy to provide analogs that could ultimately support improved pharmacological and pharmacokinetic parameters. (1824)…”
mentioning
confidence: 99%
“…(1417) Biosynthetic engineering of thiopeptides has rapidly emerged as an effective strategy to provide analogs that could ultimately support improved pharmacological and pharmacokinetic parameters. (1824)…”
mentioning
confidence: 99%
“…We have been among the groups that have reported gene clusters for the ribosome-targeting 26-membered macrocycle class (thiocillins) (28) and the EF-Tutargeting 29-membered macrocycles (GE37468) (17,18). In this study, we have turned to the 35-membered macrocycle scaffold and identified a candidate biosynthetic gene cluster for berninamycin from a draft genome sequence of the known producer Streptomyces bernensis UC 5144.…”
mentioning
confidence: 99%
“…This method may be generalized by using one of several "photo-caged" unnatural amino acids that have been developed to incorporate natural amino acids that are protected from posttranslational modification in similar fashion and subsequently postbiosynthetically deprotected to yield novel thiopeptides not otherwise expressible in vivo. Although no mutants were found with enhanced activity in this study, new chemical functionalities provided by ncAAs to thiopeptide biosynthesis offer the potential to screen a diverse chemical space for mutants with increased activity in the future (8,13).…”
Section: Discussionmentioning
confidence: 69%
“…Several methods have been used to produce thiopeptide variants, including biosynthetic pathway engineering (7,8), semisynthesis (9), and total chemical synthesis (10), with the latter providing the greatest control over chemical structure. However, the total synthesis of variants in sufficient quantities for mechanistic or therapeutic purposes is often time-consuming and costly.…”
mentioning
confidence: 99%